Synthesis, Structural Elucidation and Pharmacological Applications of Cu(II) Heteroleptic Carboxylates - Shaker Ullah; Muhammad Sirajuddin; Zafran Ullah; Afifa Mushtaq; Saba Naz; Muhammad Zubair; Ali Haider; Saqib Ali; Maciej Kubicki; Tanveer A. Wani; Seema Zargar; Mehboob Ur Rehman (Pharmaceuticals, 2023)
Six heteroleptic Cu(II) carboxylates (1–6) were prepared by reacting 2-chlorophenyl acetic acid (L1), 3-chlorophenyl acetic acid (L2), and substituted pyridine (2-cyanopyridine and 2-chlorocyanopyridine). The solid-state behavior of the complexes was described via vibrational spectroscopy (FT-IR), which revealed that the carboxylate moieties adopted different coordination modes around the Cu(II) center. A paddlewheel dinuclear structure with distorted square pyramidal geometry was elucidated from the crystal data for complexes 2 and 5 with substituted pyridine moieties at the axial positions. The presence of irreversible metal-centered oxidation reduction peaks confirms the electroactive nature of the complexes. A relatively higher binding affinity was observed for the interaction of SS-DNA with complexes 2–6 compared to L1 and L2. The findings of the DNA interaction study indicate an intercalative mode of interaction. The maximum inhibition against acetylcholinesterase enzyme was caused for complex 2 (IC50 = 2 µg/mL) compared to the standard drug Glutamine (IC50 = 2.10 µg/mL) while the maximum inhibition was found for butyrylcholinesterase enzyme by complex 4 (IC50 = 3 µg/mL) compared to the standard drug Glutamine (IC50 = 3.40 µg/mL). The findings of the enzymatic activity suggest that the under study compounds have potential for curing of Alzheimer’s disease. Similarly, complexes 2 and 4 possess the maximum inhibition as revealed from the free radical scavenging activity performed against DPPH and H2O2.